On the solid-state dewetting of polycrystalline thin films: Capillary versus grain growth approach. (15th January 2018) - Jacquet, P.; Podor, R.; Ravaux, J.; Lautru, J.; Teisseire, J.; Gozhyk, I.; Jupille, J.; Lazzari, R.
Abstract: Solid-state dewetting of polycrystalline silver thin films was investigated with in situ and real time Environmental Scanning Electron Microscopy at High Temperature (HT-ESEM) in different annealing atmospheres: secondary vacuum or oxygen-rich (partial pressure ≥100 Pa) environment. A model where oxygen plays a key role is proposed to explain the very different observed morphologies; oxygen favours hole creation and isotropic hole propagation as well as grain selection. But, whatever the atmosphere, dewetting does not proceed through the propagation of a rim but instead involves the growth of specific grains and shrinkage of others. Models based on macroscopic curvature to account for the propagation speed of the dewetting front fail to fit the present observations. This points to a paramount role of the grain size and stability in the dewetting morphology. Graphical abstract: Image 1